PROBABILISTIK PUNAHNYA MYCOBACTERIUM TUBERCULOSA YANG RESISTEN TERHADAP OBAT ANTI TUBERKULOSIS RESISTENSI PRIMER, RESISTENSI TERHADAP ISONIAZID, DAN TB–MDR DI PUSKESMAS KOTA MEDAN - Jonner Nainggolan (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2017)
In this paper, probabilistic models are developed from a dynamical model of tuberculosis transmission based on a Galton-Watson branching and Negative Binomialdistribution generation with weighted probability estimation used to test an extinction model of mycobacterium germ. The values of model parameters were obtained from the medical record data at Puskesmas Kota Medan : 31 tuberculosis patients treated during February-August 2015, with 25 sensitive samples, 3 samples of RI degree, 2 samples of RII degree, and 3 samples of RIII degree. Data analysis using Galton-Watson theorem revealed the extinction point of resistant malaria parasites, that is s = 1. The successful transmission of mycobacterium bacteria is 36 people per year. The extinction probability of mycobacterium bacteria that is resistant to anti-tuberculosis drugs is ϕNB = 1.